The Impact of Entrepreneurial Knowledge, Personality, Motivation and Family Environment on Entrepreneurial Intention Through Self Efficacy - Amaliah, Rizki; Kardoyo, Kardoyo; Rusdarti, Rusdarti (Journal of Economic Education, 2021)
Students at SMAN Jambi City, one of which is SMAN 7 and SMAN 11 Jambi City, have fewer entrepreneurial intentions. And research findings that vary from one study to another. The aim of this study was to see whether entrepreneurial knowledge, personality, motivation, and family environment impacted career intentions, both directly and indirectly, using self-efficacy as a mediator. With a sample size of 154 respondents, the study approach used was quantitative. Data collection methods was a questionnaire and documentation. Percentage descriptive and path analysis were used in the data analysis. (1) Entrepreneurial knowledge (X1) and entrepreneurial personality (X2) have a positive and important impact on entrepreneurial intention, according to data analysis. (2), while motivation (X3) and family environment (X4) have a positive and important impact on entrepreneurial intentions. (3) Self-efficacy can significantly mediate the impact of the family environment (X4), entrepreneurial knowledge (X1), entrepreneurial personality (X2), and motivation (X3) on entrepreneurial intentions by mediating the independent variables